Sex-Specific Differences in Circumpapillary Retinal Nerve Fiber Layer Thickness. - Li, D.; Rauscher, F. G.; Choi, E. Y.; Wang, M.; Baniasadi, N.; Wirkner, K.; Kirsten, T.; Thiery, J.; Engel, C.; Loeffler, M.; Elze, T. (Ophthalmology, 2020)
PURPOSE: To investigate the role of sex on retinal nerve fiber layer (RNFL) thickness at 768 circumpapillary locations based on OCT findings. DESIGN: Population-based cross-sectional study. PARTICIPANTS: We investigated 5646 eyes of 5646 healthy participants from the Leipzig Research Centre for Civilization Diseases (LIFE)-Adult Study of a predominantly white population. METHODS: All participants underwent standardized systemic assessments and ocular imaging. Circumpapillary RNFL (cRNFL) thickness was measured at 768 points equidistant from the optic nerve head using spectral-domain OCT (Spectralis; Heidelberg Engineering, Heidelberg, Germany). To control ocular magnification effects, the true scanning radius was estimated by scanning focus. Student t test was used to evaluate sex differences in cRNFL thickness globally and at each of the 768 locations. Multivariable linear regression and analysis of variance were used to evaluate individual contributions of various factors to cRNFL thickness variance. MAIN OUTCOME MEASURES: Difference in cRNFL thickness between males and females. RESULTS: Our population consisted of 54.8% females. The global cRNFL thickness was 1 mum thicker in females (P < 0.001). However, detailed analysis at each of the 768 locations revealed substantial location specificity of the sex effects, with RNFL thickness difference ranging from -9.98 to +8.00 mum. Females showed significantly thicker RNFLs in the temporal, superotemporal, nasal, inferonasal, and inferotemporal regions (43.6% of 768 locations), whereas males showed significantly thicker RNFLs in the superior region (13.2%). The results were similar after adjusting for age, body height, and scanning radius. The superotemporal and inferotemporal RNFL peaks shifted temporally in females by 2.4 degrees and 1.9 degrees , respectively. On regions with significant sex effects, sex explained more RNFL thickness variance than age, whereas the major peak locations and interpeak angle explained most of the RNFL thickness variance unexplained by sex. CONCLUSIONS: Substantial sex effects on cRNFL thickness were found at 56.8% of all 768 circumpapillary locations, with specific patterns for different sectors. Over large regions, sex was at least as important in explaining the cRNFL thickness variance as was age, which is well established to have a substantial impact on cRNFL thickness. Including sex in the cRNFL thickness norm could therefore improve glaucoma diagnosis and monitoring.
Keywords: Adult; Analysis of Variance; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Multivariate Analysis; *Nerve Fibers; Retina/*anatomy & histology; *Retinal Ganglion Cells; Sex Factors